PERAN ORGANISASI KEAGAMAAN DALAM PEMBERDAYAAN EKONOMI KELOMPOK MASYARAKAT (POKMAS) PEREMPUAN BERBASIS MODAL SOSIAL - Khumaidi Khumaidi (Muwazah, 2011)
Abstract : This writing is to show how women religion organization hasÂ  an interlationshipÂ  use social capital by giving economical benefit to green vendors in local term called â€œMlijoâ€ in Malang. Social capital which performs social informal relationship, also contribute to the proses of how the community group help others aspecially women green vendors as community group which have role in rising fund to empower their efforts.